2020
DOI: 10.3390/cancers12040894
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Perspective on Current Prognostic and Predictive Biomarkers in Chronic Lymphocytic Leukemia in the Context of Chemoimmunotherapy and Novel Targeted Therapy

Abstract: Chronic lymphocytic leukemia (CLL) is a heterogeneous disease with a variable clinical course. Novel biomarkers discovered over the past 20 years have revolutionized the way clinicians approach prognostication and treatment especially in the chemotherapy-free era. Herein, we review the best established prognostic and predictive biomarkers in the setting of chemoimmunotherapy (CIT) and novel targeted therapy. We propose that TP53 disruption (defined as either TP53 mutation or chromosome 17p deletion), unmutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 131 publications
1
21
0
2
Order By: Relevance
“…In addition, the analysis of TP53 mutations can identify 30-40% of CLL patients who only carry the gene mutations and may be missed by FISH. Cohen et al proposed that TP53 aberrations, unmutated IGHV , mutated NOTCH1 and CD49d expression are powerful prognosticators and have predictive significance in CLL before treatment initiation to guide therapeutic decisions ( 28 ). IGHV mutational status is a stable CLL prognostic marker and can be measured at any time throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analysis of TP53 mutations can identify 30-40% of CLL patients who only carry the gene mutations and may be missed by FISH. Cohen et al proposed that TP53 aberrations, unmutated IGHV , mutated NOTCH1 and CD49d expression are powerful prognosticators and have predictive significance in CLL before treatment initiation to guide therapeutic decisions ( 28 ). IGHV mutational status is a stable CLL prognostic marker and can be measured at any time throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…The prominent tumor suppressor gene TP53 is located in the band 17p13. TP53 disruption relates to unfavorable prognosis in CLL patients [76]. The overexpression of a novel oncogene maternal embryonic leucine zipper kinase (MELK) predicts inferior survival in CLL and correlates with deletion of 17p13, as well as higher WBC count, advanced stage, elevated LDH, increased β2-M, unmutated IGHV status and positive ZAP70 [77].…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Our data showed that the low expression of ZHX1 and ZHX2 is associated with a worse prognosis in CLL, followed by a greater number of leukemic cells and unfavorable cytogenetics findings in the diagnosis [5]. Recently, several studies have been conducted to unravel the influence of members of the ZHX family on cancer.…”
mentioning
confidence: 61%